Depressão e isolamento social na velhice: identificação de sinais na consulta de enfermagem e estratégias de acolhimento - Narcy Miranda Batista Nakamura; Andrea Cristina Rocha; Adriana Rosa da Silva Santos; Maria Aparecida de Oliveira Tannus; Floripes Inácio da Silva; Maria José da Silva Martins; Eliane June Maia; Amanda Serrano Garcia; Ana Paula de Figueiredo; Oldair Donizete Galeni; Luciana dos Santos Rodrigues Pires (Revista ft, 2026)
Population ageing is an important demographic phenomenon that poses new challenges to health services, particularly regarding the identification and care of mental disorders among older adults. Among these conditions, depression is particularly relevant because of its impact on autonomy, functional capacity, quality of life, and social relationships, and may be associated with loneliness and social isolation. In this context, nursing consultations represent a strategic opportunity for the early identification of emotional, behavioral, and social changes that may indicate psychological distress. This study aims to analyze the relationship between depression and social isolation in old age, highlighting signs that can be identified during nursing consultations and the main welcoming and care strategies. This is a narrative literature review with a qualitative and descriptive approach, based on scientific publications and institutional documents related to mental health, ageing, Primary Health Care, and nursing care for older adults. The literature indicates that social isolation, emotional losses, reduced autonomy, chronic diseases, and weakened support networks may contribute to greater vulnerability to psychological distress. It is concluded that nurses, through qualified listening, multidimensional assessment, strengthening of therapeutic bonds, identification of risk factors, and coordination with families and multidisciplinary teams, can contribute to the early recognition of symptoms and to comprehensive and humanized care for older adults.